2018
DOI: 10.1007/s00784-018-2554-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical property investigation of contemporary glass ionomer and resin-modified glass ionomer restorative materials

Abstract: As compared to RMGI materials, conventional glass ionomer restorative materials demonstrate more stability in physical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 86 publications
0
39
0
3
Order By: Relevance
“…For example, the fracture toughness at 24 h of a number of commercial conventional glass-ionomers ranged from 0.18 to 0.30 MPa m 1 /2 compared with 0.49-0.67 MPa m 1 /2 for a similar set of commercial RMGICs. For the same materials, flexural strength at 24 h ranged from 18 to 34 MPa for the conventional glass-ionomers compared with 49-76 MPa for the RMGICs [40]. These differences are attributable to the presence of the polymerized resin component, which toughens the cement and improves its ability to withstand loading in flexure.…”
Section: Mechanical Properties Of Conventional and Resin-modified Glamentioning
confidence: 97%
See 1 more Smart Citation
“…For example, the fracture toughness at 24 h of a number of commercial conventional glass-ionomers ranged from 0.18 to 0.30 MPa m 1 /2 compared with 0.49-0.67 MPa m 1 /2 for a similar set of commercial RMGICs. For the same materials, flexural strength at 24 h ranged from 18 to 34 MPa for the conventional glass-ionomers compared with 49-76 MPa for the RMGICs [40]. These differences are attributable to the presence of the polymerized resin component, which toughens the cement and improves its ability to withstand loading in flexure.…”
Section: Mechanical Properties Of Conventional and Resin-modified Glamentioning
confidence: 97%
“…Despite these variations in reported values in individual papers, there does seem to be an overall consensus that RMGICs are superior to conventional materials in their diametral tensile strength [38,39] and in their flexural strength [39]. In a recent study, the superiority of the toughness and flexural properties was shown to be consistent across a range of brands [40]. For example, the fracture toughness at 24 h of a number of commercial conventional glass-ionomers ranged from 0.18 to 0.30 MPa m 1 /2 compared with 0.49-0.67 MPa m 1 /2 for a similar set of commercial RMGICs.…”
Section: Mechanical Properties Of Conventional and Resin-modified Glamentioning
confidence: 99%
“…RMGIC has greater mechanical resistance and better physical properties, but it has clinical limitations such as decreased biocompatibility [22][23][24] due to the presence of the 2-hydroxyethyl methacrylate (HEMA) monomer, which is considered cytotoxic in contact with the pulp tissue, thus limiting its use in deep cavities. This monomer is capable of inducing apoptosis by increasing oxidative stress induced by an excess of reactive oxygen species, damage to DNA, and suppression of cell proliferation [25].…”
Section: Discussionmentioning
confidence: 99%
“…The porosity of the material is also an important property to be evaluated as it is related to the degree of dissolution and, consequently, to the resistance of the restorative material, which can alter its clinical durability. The increase in porosity also results in increased material roughness and greater adhesion of microorganisms [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation